2015
DOI: 10.1080/2162402x.2015.1078055
|View full text |Cite
|
Sign up to set email alerts
|

Formylpeptide receptor 1 mediates the tumorigenicity of human hepatocellular carcinoma cells

Abstract: G protein-coupled chemoattractant receptors (GPCRs) have been implicated in cancer progression. Formylpeptide receptor 1 (FPR1) was originally identified as a GPCR mediating anti-microbial host defense. However, the role of FPR1 in tumorigenesis remains poorly understood. The current study aims to investigate the potential of FPR1 to regulate human hepatoma growth and invasion. We found the FPR1 gene and protein expression in human intratumoral and peritumoral tissues of hepatocellular carcinoma (HCC) specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“… 7 , 8 , 25 , 26 Database analyses revealed that FPR1 expression levels are upregulated in malignant glioma cells, colon cancer, lung cancer and hepatocellular carcinoma cells compared with those in normal controls. 27 30 According to our results, FPR1 was also overexpressed in tumor tissues from terminal-stage cervical cancer patients and from patients with poor prognosis. These observations indicated that FPR1 expression levels may serve as a diagnostic marker for cervical cancer.…”
Section: Discussionmentioning
confidence: 56%
“… 7 , 8 , 25 , 26 Database analyses revealed that FPR1 expression levels are upregulated in malignant glioma cells, colon cancer, lung cancer and hepatocellular carcinoma cells compared with those in normal controls. 27 30 According to our results, FPR1 was also overexpressed in tumor tissues from terminal-stage cervical cancer patients and from patients with poor prognosis. These observations indicated that FPR1 expression levels may serve as a diagnostic marker for cervical cancer.…”
Section: Discussionmentioning
confidence: 56%
“…The in vitro wound-healing assays were carried out as we have previously published (35). Briefly, we created a gap in the monolayer of the attached THP-1-differentiated macrophages.…”
Section: Scratch Wound-healing Modelmentioning
confidence: 99%
“…For example, FPR1 expression is associated with tumor progression and survival in gastric cancer [15], and FPR1 mediates the tumorigenicity of human hepatocellular carcinoma cells [16]. High expression of FPR1 in neuroblastoma primary tumors corresponds with high-risk disease and poor patient survival [17].…”
Section: Introductionmentioning
confidence: 99%